2020
DOI: 10.1111/iej.13307
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the addition of surfactants to sodium hypochlorite on the removal of hard tissue debris

Abstract: AimTo evaluate the effect of the addition of surfactants to sodium hypochlorite (NaOCl) on the removal of accumulated hard tissue debris (AHTD), before and after final irrigation with 17% EDTA, from mesial canals of mandibular molars through microcomputed tomographic (micro‐CT) analysis.MethodologyThirty moderately curved mandibular mesial roots with Vertucci type II canal configuration were selected and scanned in a micro‐CT device at an isotropic resolution of 22.9 μm. The specimens were assigned to three gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Regarding chelating agents, previous studies showed an additional effect of EDTA in removing AHTD. 17,36 In this systematic review, the irrigation with a chelating agent (EDTA) was found to be performed in two 29,31 of the three selected studies.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding chelating agents, previous studies showed an additional effect of EDTA in removing AHTD. 17,36 In this systematic review, the irrigation with a chelating agent (EDTA) was found to be performed in two 29,31 of the three selected studies.…”
Section: Discussionmentioning
confidence: 99%
“…Its success depends on broader principles, for which sufficient mechanical preparation, thorough disinfection and obturation with no voids are important [ 1 , 2 ]. Accumulated hard tissue debris (AHTD) is produced during the mechanical preparation process and pile up in the root canal system, which usually compromise the success of endodontic treatment [ 3 , 4 ]. Research has shown that root canal irrigation helps to remove AHTD; however, no irrigation protocol has been found to completely remove AHTD due to the anatomical complexity of the root canal system, especially in isthmus and apical regions [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sodium hypochlorite (NaOCl) is the most used irrigant during root canal preparation due to its high capacity for tissue dissolution and a well-known antimicrobial activity [ 12 ]. Surfactants are associated with NaOCl to improve its properties, such as dissolution of organic tissues, antimicrobial activity and penetration into the root canal system [ 13 ].…”
Section: Introductionmentioning
confidence: 99%